Metagenomic and PCR-Based Diversity Surveys of [FeFe]-Hydrogenases Combined with Isolation of Alkaliphilic Hydrogen-Producing Bacteria from the Serpentinite-Hosted Prony Hydrothermal Field, New Caledonia - Mei, Nan; Postec, Anne; Monnin, Christophe; Pelletier, Bernard; Payri, Claude E.; Ménez, Bénédicte; Frouin, Eléonore; Ollivier, Bernard; Erauso, Gaël; Quéméneur, Marianne (Frontiers in Microbiology, 2016)
High amounts of hydrogen are emitted in the serpentinite-hosted hydrothermal field of the Prony Bay (PHF, New Caledonia), where high-pH (~11), low-temperature (< 40°C), and low-salinity fluids are discharged in both intertidal and shallow submarine environments. In this study, we investigated the diversity and distribution of potentially hydrogen-producing bacteria in Prony hyperalkaline springs by using metagenomic analyses and different PCR-amplified DNA sequencing methods. The retrieved sequences of hydA genes, encoding the catalytic subunit of [FeFe]-hydrogenases and, used as a molecular marker of hydrogen-producing bacteria, were mainly related to those of Firmicutes and clustered into two distinct groups depending on sampling locations. Intertidal samples were dominated by new hydA sequences related to uncultured Firmicutes retrieved from paddy soils, while submarine samples were dominated by diverse hydA sequences affiliated with anaerobic and/or thermophilic submarine Firmicutes pertaining to the orders Thermoanaerobacterales or Clostridiales. The novelty and diversity of these [FeFe]-hydrogenases may reflect the unique environmental conditions prevailing in the PHF (i.e., high-pH, low-salt, mesothermic fluids). In addition, novel alkaliphilic hydrogen-producing Firmicutes (Clostridiales and Bacillales) were successfully isolated from both intertidal and submarine PHF chimney samples. Both molecular and cultivation-based data demonstrated the ability of Firmicutes originating from serpentinite-hosted environments to produce hydrogen by fermentation, potentially contributing to the molecular hydrogen balance in situ.